Outcomes of Flexible Ureterorenoscopy and Laser Fragmentation for Renal Stones: Comparison Between Digital and Conventional Ureteroscope - Somani, Bhaskar K.; Al-Qahtani, Saeed M.; Gil de Medina, Sixtina Diez; Traxer, Olivier (Urology (Ridgewood, N.J.), 2013)
To compare the outcomes of flexible ureterorenoscopy and lasertripsy (FURS) using digital and conventional FURS for kidney stones. From September 2007 to April 2011, 118 patients underwent FURS (by the same surgeon). The outcomes were compared between equal numbers of procedures (59 each) using a conventional flexible ureterorenoscope (C-FURS; Olympus URF-P5) and a digital flexible ureterorenoscope (D-FURS; Olympus URF-V). Although the deflection, working channel, and field view are similar in both, the initial and terminal diameter is 8.4F and 9.9F and 6.9F and 8.4F for the D-FURS and C-FURS, respectively. The mean stone fragmentation time was calculated by the size per operative time. The preoperative, operative, and postoperative data were retrospectively analyzed and compared. The patient demographics were comparable. The mean stone size was 12.8 and 12 mm in the C-FURS and D-FURS groups, respectively. The initial assessment of the entire pyelocaliceal system was possible in 58 of 59 cases (98%) in the C-FURS group and 56 of 59 cases (94%) in the D-FURS group. The mean operative time was significantly longer in the C-FURS group (53.8 ± 15.2 minutes vs 44.5 ± 14.9 minutes). The overall stone-free rate 1 month after the procedure was 86% in the C-FURS group and 88% in the D-FURS group. Although on comparison, the D-FURS had slightly limited maneuverability, comparable success rates can be achieved with both conventional and digital ureteroscopes. D-FURSs significantly reduced the operative time compared with C-FURSs.